Pengaruh Komponen Keputusan Keuangan Terhadap Nilai Perusahaan - Bernarda Kriswulan Bucharni; Swarmilah Hariani (LPMP Imperium, 2021)
This research was conducted to analyze the impact of investment decisions, funding decisions, and dividend decisions on firm value. The object of this research is the sector of trading and service companies listed on the Indonesia Stock Exchange. The sampling method in this research used the purposive sampling technique to get as many as 70 samples. The data analysis process used multiple linear regression analysis models processed by SPSS 25 application software. The results of this research indicate that investment decisions and dividend decisions have a significant positive effect on firm value. Meanwhile, funding decisions do not affect firm value.